Pancreatic alpha cells in diabetic rats express active GLP-1 receptor: Endosomal co-localization of GLP-1/GLP-1R complex functioning through intra-islet paracrine mechanism - Nakashima, Koji (Sci Rep, 2018)
Glucagon-like peptide-1 (GLP-1) stimulates insulin secretion from pancreatic beta cells and suppresses glucagon secretion from alpha cells. It remains controversial, however, whether GLP-1 receptor (GLP-1R) is expressed in mature alpha cells. In this study, unlike previous studies using non-diabetic animals, we demonstrated using diabetic model rats and confocal laser scanning microscopy that the GLP-1/GLP-1R complex was located in the endosome of diabetic islets. In addition, we showed that GLP-1 and GLP-1R co-localized with various endosomal markers and adenylate cyclase in the alpha cells of diabetic rats. Diabetic rats had endosomal signaling pathway but normal rats had classical signaling pathway for activated GLP-1R. Furthermore, we performed pancreatic perfusion to assess the functional activity of GLP-1R when stimulated by exendin-4 (EX4). In a pancreas perfusion study, EX4 significantly stimulated glucagon secretion in diabetic rats but not normal rats. However, such glucagon secretion was immediately suppressed, probably due to concomitantly secreted insulin. The GLP-1/GLP-1R complex appears to function through an intra-islet paracrine mechanism in diabetic conditions which could explain, at least in part, the mechanism of paradoxical hyperglucagonaemia in type 2 diabetes.